2018
DOI: 10.1111/rssa.12423
|View full text |Cite
|
Sign up to set email alerts
|

Information-Anchored Sensitivity Analysis: Theory and Application

Abstract: Summary Analysis of longitudinal randomized clinical trials is frequently complicated because patients deviate from the protocol. Where such deviations are relevant for the estimand, we are typically required to make an untestable assumption about post‐deviation behaviour to perform our primary analysis and to estimate the treatment effect. In such settings, it is now widely recognized that we should follow this with sensitivity analyses to explore the robustness of our inferences to alternative ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…These results are in line with the theory for continuous data (Cro et al), which shows that the approximation of Rubin's rules to information anchoring improves as the treatment effect decreases. To explore this further, we now consider additional scenarios.…”
Section: Simulation Studysupporting
confidence: 90%
See 2 more Smart Citations
“…These results are in line with the theory for continuous data (Cro et al), which shows that the approximation of Rubin's rules to information anchoring improves as the treatment effect decreases. To explore this further, we now consider additional scenarios.…”
Section: Simulation Studysupporting
confidence: 90%
“…In the context of longitudinal data, Carpenter et al sketch that, because distributional information is borrowed under reference‐based methods, the standard likelihood calculation results in an artificial gain in statistical information about the treatment effect, relative to what we would expect to see if the missing data were able to be actually observed, and their distribution corresponded to that under the reference‐based assumption. By contrast, they propose, and Cro et al prove, that for continuous longitudinal data using Rubin's rules is—to a good approximation— information anchored . This means that reference‐based imputation using Rubin's rules in the conventional way approximately preserves the fraction of information lost due to missing data across each of the assumptions.…”
Section: Simulation Studymentioning
confidence: 97%
See 1 more Smart Citation
“…2, panel A, region b). The ranges associated with each category of symptoms were drawn from published literature: 'mild' (1-10), 'moderate' (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), 'moderate to severe' (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 'severe' (36-51). Figure 2, panel A, region a, shows illustrative results from an elicitation.…”
Section: Symptom Severity Scalementioning
confidence: 99%
“…Controlled multiple imputation also provides an accessible, exible tool for contextually relevant sensitivity analysis which is the next and nal key step when handling missing outcome data during a pandemic. We have previously shown that the aforementioned controlled procedures (delta-and reference-based multiple imputation) provide valid inference, as the proportion of information lost due to missing data under MAR is approximately preserved in the analysis (21); That is information anchored inference will be obtained.…”
Section: Participants Lost To Follow-up During Pandemic Times (Iii)mentioning
confidence: 99%